Theory, Practice, and Non-reductive (Meta)Science. Issue 2 (3rd April 2018) - Sanches de Oliveira, Guilherme
Abstract: Are the theoretical frameworks of phenomenology and of science compatible? And, if so, what would a reconciliation entail for science as it is practiced ? Gallagher [2019 ] poses these two questions, answering the first in the affirmative and leaving the second unaddressed. I argue that treating the two as separate questions presupposes an inadequate distinction between theory and practice that Gallagher's non-reductive framework motivates rejecting. Recognizing the intertwining of theory and practice allows us to answer Gallagher's two questions about phenomenology and science all at once, but it also motivates a less conciliatory conclusion than the one he offers.